Primary and Metastatic Pancreatic Ewing Sarcomas: A Case Report and Review of the Literature - Nektarios I. Koufopoulos; Menelaos G. Samaras; Christakis Kotanidis; Konstantinos Skarentzos; Abraham Pouliakis; Ioannis Boutas; Adamantia Kontogeorgi; Magda Zanelli; Andrea Palicelli; Maurizio Zizzo; Giuseppe Broggi; Rosario Caltabiano; et al. (Diagnostics)
Ewing sarcomas are rare tumors arising mainly in the bones and the surrounding soft tissues. Primary extraosseous Ewing sarcomas have also been described in several other organs and locations other than bones, including the pancreas. These tumors have well-defined histological, immunohistochemical, and molecular characteristics. In this manuscript, we present a case of primary Ewing sarcoma of the pancreas in a 29-year-old patient, and we systematically review the literature on both primary and metastatic Ewing sarcomas of the pancreas, describing their clinicopathological characteristics. We also discuss the differential diagnosis and the treatment of this rare entity.